Distribution system with wind penetration - Ernesto Jair Eguis-Eslava; Kelly Marcela Padilla-García; Luis Alberto López-Díaz; José Daniel Soto-Ortiz; Rafael Castillo-Sierra; Mauricio Pardo-González; Cesar Augusto Orozco-Henao; Elvin Arnaldo Jiménez-Matos; Ingrid Oliveros-Pantoja (Visión Electrónica, 2019)
This article presents the results of the analysis of the studies of the operation of a modified IEEE-13 distribution feeder, which was built to scale in the laboratory at Universidad del Norte. In this article, we show the cases of the operating regimes of the modified IEEE-13, before the different levels of wind energy penetration. The modified IEEE-13 distribution feeder was built taking into account that each of the scaled modules and their generator-load will work under the conditions of the Universidad del Norte laboratory. An experimental methodology was used to compare the results obtained in the actual scaled model with the results of the simulations in specialized programs. The conclusions of the article show the wind energy that can be injected into an electrical system with conventional power generation so that it can maintain its operation complying with the current regulatory framework.